2009
DOI: 10.1186/1756-8722-2-48
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Myeloma Involving Skin and Pulmonary Parenchyma after Autologous Stem Cell Transplantation

Abstract: Pulmonary involvement and skin involvement are rare complications of plasma cell neoplasms. Here we describe what may be the first reported case of a patient with relapse in both of these sites following autologous peripheral blood stem cell transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…11 In addition, only a few cases with histologically proven pulmonary involvement have been reported in the literature. [12][13][14][15][16][17][18] These findings suggest that the histological diagnosis of pulmonary involvement in myeloma is extremely difficult, particularly after bortezomib treatment, as in the present case. In patients with multiple myeloma who manifest abnormal pulmonary shadowing, pulmonary involvement from myeloma cells may be possible; therefore, lower doses of bortezomib should be initially administered to avoid severe DAH.…”
Section: Discussionsupporting
confidence: 54%
“…11 In addition, only a few cases with histologically proven pulmonary involvement have been reported in the literature. [12][13][14][15][16][17][18] These findings suggest that the histological diagnosis of pulmonary involvement in myeloma is extremely difficult, particularly after bortezomib treatment, as in the present case. In patients with multiple myeloma who manifest abnormal pulmonary shadowing, pulmonary involvement from myeloma cells may be possible; therefore, lower doses of bortezomib should be initially administered to avoid severe DAH.…”
Section: Discussionsupporting
confidence: 54%
“…In the majority of cases reviewed, the diagnosis was either made via biopsy (trans-bronchial or surgical) or at autopsy . However, two cases were reported in the literature of BAL flow cytometry revealing monoclonal plasma cells in patients who had histologically proven myelomatous involvement of the pulmonary parenchyma [3,5]. These two cases, along with the case we have presented, suggest that evaluation of BAL samples could help establish the diagnosis and avoid the need for more invasive biopsy techniques.…”
mentioning
confidence: 64%
“…Other manifestations of pulmonary involvement in multiple myeloma include pneumonia, mass lesion, interstitial disease and calcification. Review of the literature revealed seven case reports of patients with MM found to have interstitial pulmonary infiltration with neoplastic plasma cells, of which two were the initial presentation of myeloma and five were in patients previously diagnosed and treated [3][4] The diagnosis of extramedullary dissemination in the lungs can be determined by bronchoalveolar lavage (monclonal plasma cells are found) or lung biopsy (interstitial infiltrate of plasma cells) [7]. Our patient's BAL results revealed monoclonal plasma cells on microscopic examination smear / cytospin.…”
Section: He Was Diagnosed With Multiple Myeloma Igamentioning
confidence: 99%
“…While pulmonary findings in MM are relatively common, the overwhelming majority of these are related to an infectious etiology [ 3 ]. Review of the literature revealed seven case reports of patients with MM found to have interstitial pulmonary infiltration with neoplastic plasma cells, of which two were the initial presentation of myeloma and five were in patients previously diagnosed and treated [ [4] , [5] , [6] , [7] , [8] , [9] , [10] ]. The clinical picture can also differ significantly, from a more insidious onset of cough and shortness of breath to a rapidly progressive presentation resembling the Acute Respiratory Distress Syndrome (ARDS) [ 6 , [8] , [9] , [10] ].…”
Section: Discussionmentioning
confidence: 99%